Preference for control in rural Mexican and urban Anglo American children - Kagan, Spencer (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Urban United States and rural Mexican boys and girls were individually presented with a novel behavioral measure, the Preference for Control Wheel, to assess both their preference for control and their perception of locus of control. Due to an illusion, almost all children had an internal perception of locus of control. Nevertheless, urban United States children significantly more than rural Mexican children attempted to control the wheel of chance. Boys of both cultures attempted to control the wheel more than girls, but that difference did not reach significance. Results were related to Rotter’s social learning theory, Festinger’s dissonance theory, and cultural comparisons of child-rearing practices.